Territorio, memoria y relato En la construcción de entidades colectivas - DAVILO, Beatríz; GERMAIN, Marisa; GOTTA, Claudia; MANAVELLA, Analía; MUGICA, María Luisa (UNIVERSIDAD NACIONAL DE ROSARIO, 2004)
Colaboradores: AÑON, Valeria; BONANO, Mariana; BREZZO, Liliana; CONTARDI, Sonia; COPES, Ana; VALLEJOS, Celina; BARON, Claudia; ORTIZ, Graciela; ACUÑA, Lidia; BOLCATTO, Andrea; ROMERO, Luis Alberto; MONTINI, Pablo; PAMPINELLA, Silvia; GRACIANO, Osvaldo